Removal of methylene blue and copper (ii) by oil palm empty fruit bunch sorbents - Mohd. Nasir, Nur Haziqah (Penerbit UTM Press, 2015)
This study aims to evaluate the adsorptive properties of oil palm empty fruit bunch for the removal of cationic pollutants in water. The untreated and hydrochloric acid-treated empty fruit bunches were characterized based on pH of adsorbent, specific surface area and surface functional groups. The adsorbents were then used to challenge varying concentrations of methylene blue dye and copper (II) in aqueous solution. Results show that the specific surface area of empty fruit bunch decreased upon the treatment with hydrochloric acid. The untreated adsorbent displays a higher equilibrium removal of the target pollutants due to its higher specific surface area of 28.4 m2/g. The maximum removal were recorded as 0.103 and 0.075 mmol/g for methylene blue and copper (II), respectively. Oil palm empty fruit bunch is a promising candidate for the removal of cationic pollutants in aqueous solution.